An approach to gene-specific transcription inhibition using oligonucleotides complementary to the template strand of the open complex - Milne, Lisa (The National Academy of Sciences, 2000)
The single-stranded region of DNA within the open complex of transcriptionally active genes provides a unique target for the design of gene-specific transcription inhibitors. Using the Escherichia coli lac UV5 and trp EDCBA promoters as in vitro models of open complex formation, we have identified the sites inside these transcription bubbles that are accessible for hybridization by short, nuclease-resistant, nonextendible oligoribonucleotides (ORNs). Binding of ORNs inside the open complex was determined by linking the chemical nuclease bis(1,10-phenanthroline) cuprous chelate [(OP)(2)Cu(+)] to the ORN and demonstrating template-specific DNA scission. In addition, these experiments were supported by in vitro transcription inhibition. We find that the most effective inhibitors are 5 nt long and have sequences that are complementary to the DNA template strand in the region near the transcription start site. The ORNs bind to the DNA template strand, forming an antiparallel heteroduplex inside the open complex. In this system, RNA polymerase is essential not only to melt the duplex DNA but also to facilitate hybridization of the incoming ORN. This paradigm for gene-specific inactivation relies on the base complementarity of the ORN and the catalytic activity and sequence specificity of RNA polymerase for the site- and sequence-specific recognition and inhibition of transcriptionally active DNA.